2021
DOI: 10.1007/s00526-021-02043-0
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity of the Hopf fibration

Abstract: In this paper, we study minimal maps between euclidean spheres. The Hopf fibrations provide explicit examples of such minimal maps. Moreover, their corresponding graphs have second fundamental form of constant norm. We prove that a minimal submersion from S 3 to S 2 whose Gauss map satisfies a suitable pinching condition must be weakly conformal with totally geodesic fibers. As a consequence, we obtain that an equivariant minimal submersion from S 3 to S 2 coincides with the Hopf fibration. Furthermore, we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The map f is harmonic when we equip S 3 with the graphical metric g = g S 3 +f * g S 2 , where g S 3 is the metric of S 3 and g S 2 is the metric of S 2 . It seems that the methods developed in the present paper cannot be easily used, since in the structure equations (2.1) the curvature operator of the graphical metric shows up; for more information regarding this problem we refer to [17]. (e) In [19] it is shown that the graphical mean curvature flow (GMCF) will smoothly deform any strictly length decreasing map h : S 2 → S 2 into a constant map.…”
Section: Uniqueness Of the Hopf Fibrationmentioning
confidence: 97%
See 1 more Smart Citation
“…The map f is harmonic when we equip S 3 with the graphical metric g = g S 3 +f * g S 2 , where g S 3 is the metric of S 3 and g S 2 is the metric of S 2 . It seems that the methods developed in the present paper cannot be easily used, since in the structure equations (2.1) the curvature operator of the graphical metric shows up; for more information regarding this problem we refer to [17]. (e) In [19] it is shown that the graphical mean curvature flow (GMCF) will smoothly deform any strictly length decreasing map h : S 2 → S 2 into a constant map.…”
Section: Uniqueness Of the Hopf Fibrationmentioning
confidence: 97%
“…Consequently, g is a conformal map. This implies that the graph of g is a minimal surface in S 2 − × S 2 + ; see for example [2, Proposition 4.5.3], [7] or [17]. On the other hand, g is strictly length decreasing.…”
Section: 3mentioning
confidence: 99%